Outcomes of an integrated practice unit for vulnerable emergency department patients - Deepa Borde; Denny Fe G. Agana-Norman; Robert Leverence; Lorrie Photos; Jon Shuster; Kiran Lukose; Jacqueline Pinkney; Joy Wright; Lori Waxenberg; Brandon Allen; Nila S. Radhakrishnan (BMC, 2023)
Abstract Background An integrated practice unit (IPU) that provides a multidisciplinary approach to patient care, typically involving a primary care provider, registered nurse, social worker, and pharmacist has been shown to reduce healthcare utilization among high-cost super-utilizer (SU) patients or multi-visit patients (MVP). However, less is known about differences in the impact of these interventions on insured vs. uninsured SU patients and super high frequency SUs ( $$\ge$$ 8 ED visits per 6 months) vs. high frequency SUs (4-7 ED visits per 6 months). Methods We assessed the percent reduction in ED visits, ED cost, hospitalizations, hospital days, and hospitalization costs following implementation of an IPU for SUs located in an academic tertiary care facility. We compared outcomes for publicly insured with uninsured patients, and super high frequency SUs with high frequency SUs 6 months before vs. 6 months after enrollment in the IPU. Results There was an overall 25% reduction in hospitalizations (p < 0.001), and 23% reduction in hospital days (p = 0.0045), when comparing 6 months before vs. 6 months after enrollment in the program. There was a 26% reduction in average total direct hospitalization costs per patient (p = 0.002). Further analysis revealed a greater reduction in health care utilization for uninsured SU patients compared with publicly insured patients. The program reduced hospitalizations for super high frequency SUs. However, there was no statistically significant impact on overall health care utilization of super high frequency SUs when compared with high frequency SUs. Conclusions Our study supports existing evidence that dedicated IPUs for SUs can achieve significant reductions in acute care utilization, particularly for uninsured and high frequency SU patients. Trial Registration IRB201500212. Retrospectively registered.